The court, consumerism and the defendant - Raine, John W. (The British journal of criminology, 1996)
This article explores the scope for developing consumerist principles in the context of the courts and their treatment of defendants. An initiative at Bexley Magistrates Court is described as a case-study in this respect involving pre-hearings for defendants where advice and assistance are given in applying for legal aid and in obtaining the services of a solicitor. The article presents some results of research which evaluated the initiative; highlights the main impacts for defendants; raises important questions about consumerist approaches within the judicial context, particularly in relation to the independence and neutrality of the court, and concludes by proposing how potential conflict here might best be addressed